Teologi Bencana Dalam Al-Qur’an - Muhadi Zainuddin (Universitas Islam Indonesia, 2013)
This article tries to explain the theological perspective of disaster in holy Qur’an. Some terms that used which refer to disaster, there are: mushibah, bala, fitnah and adzab. Each term has special meaning and stressing. In the quranic term, disaster sometimes happen due to human actions that damage ecosystems and sometimes sent down directly by God to test His servants who believe.